2016
DOI: 10.1007/s00268-016-3574-2
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound‐Guided Placement of Central Venous Port Systems via the Right Internal Jugular Vein: Are Chest X‐Ray and/or Fluoroscopy Needed to Confirm the Correct Placement of the Device?

Abstract: Ultrasonography has resulted in improved safety and effectiveness of port system implantation. The routine use of CXR and IF should be considered unnecessary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
37
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(37 citation statements)
references
References 42 publications
0
37
0
Order By: Relevance
“…Firstly, we included far more CVC placements (2602 vs 1553) and studies (25 vs 15). Secondly, a strength of our study was that we included studies that used alternative reference standards; TEE, computed tomography, and intra-fluoroscopy were utilized in addition to CXR [ 26 , 27 , 46 ]. Thirdly, our study provides an accurate overview of the various US protocols used and their accuracy.…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, we included far more CVC placements (2602 vs 1553) and studies (25 vs 15). Secondly, a strength of our study was that we included studies that used alternative reference standards; TEE, computed tomography, and intra-fluoroscopy were utilized in addition to CXR [ 26 , 27 , 46 ]. Thirdly, our study provides an accurate overview of the various US protocols used and their accuracy.…”
Section: Discussionmentioning
confidence: 99%
“…There are no standard formulas to predict the exact catheter insertion length, and although the average length in adults via the right IJV is 13 to 16 cm, there are no specific range or average measurements for children. 11,12 However, this study showed an excellent reliability of the estimated catheter tip placement using USG, anatomic landmarks, and EKG monitoring. These data allow us to state that the use of IF could be restricted to selected children, when serious doubts about catheter placements arise, or if symptoms of malposition or migration should occur.…”
Section: Discussionmentioning
confidence: 69%
“…Other authors have studied the need for protocol for chest X-ray or IF for CVP placement in adult patients deeming them unnecessary, resulting in lower cost of the procedure, as well as reducing cumulative radiation dose. 11,13 Miccini et al 11 in 2016 used a formula for estimating catheter length (patient height/10-2 cm) and USG for CVP placement in 304 patients, with catheter malposition encountered in only 4 patients. Wang et al 14 proposed p-wave amplitude monitoring through intracavitary EKG monitoring to improve the accuracy of catheter tip placement without the need of radiation exposure.…”
Section: Discussionmentioning
confidence: 99%
“…A prospective evaluation of 302 adult patients who underwent elective central venous port system (CVPS) placement through the right internal jugular vein under USG found no unexpected misplacement during intraoperative fluoroscopy that had not been detected with ultrasound (US) before. Intraoperative fluoroscopy only confirmed the correct position of catheters in all cases [10]. So, the authors concluded that the routine use of fluoroscopy is unnecessary.…”
Section: Discussionmentioning
confidence: 90%